The Distribution of Mexico's Public Spending on Education - Salinas, Angel (The World Bank, 1999)
July 2000 - Public spending on tertiary education in Mexico is strongly regressive, benefiting mainly the nonpoor in urban areas. To give the poor a chance at higher education, student loan programs or means-tested financial aid and scholarship programs (though rarely devoid of subsidy) are preferable to free education services, because loan and aid programs target the students who suffer from the financial market's failure to provide long-term loans for higher education. Research shows that education has played a crucial role in raising levels of earnings and that returns to education in Mexico have increased, particularly in higher education and in the upper tail of the conditional earnings distribution. Lopez-Acevedo and Salinas examine patterns of public spending on education in the face of further increases in earnings inequality. They analyze the incidence of benefits using two sets of data: data on unit costs per student by state and by education level, and data from surveys on household income and spending. Among their findings: · Nationally, the poorest income groups get most of the national and state subsidy for primary education. At higher education levels the poor get progressively smaller subsidies. · For all Mexico, government spending on primary education is very progressive. In lower secondary education it is neutral. And in upper secondary education it benefits mainly the middle and upper classes. Tertiary education is strongly regressive, benefiting mainly the richest deciles and mainly in urban areas. · But those government patterns vary by region. In the central region average total spending is more uniformly distributed than the national pattern. In the northern region the subsidy is progressive. Primary education is neutral and higher levels of instruction are moderately regressive.